involucramiento ciudadano en el fortalecimiento de la gestión social de la parroquia casacay del cantón pasaje, 2024. - Saquipay Erraez, Silvio Joel; Gonzalez Herrera, Brigitte Silvana (Machala, 2025)
The present work addresses the incidence of citizen involvement in the strengthening of social management in the parish of Casacay, belonging to the canton of Pasaje. The work focuses on identifying the barriers and challenges that limit the active participation of the inhabitants in community decision-making, as well as on proposing strategies that promote greater commitment and social cohesion in the region. The central problem identified lies in the limited citizen involvement, a situation that negatively affects the community's ability to organise and address common problems effectively. Among the main factors that contribute to this problem are the lack of trust in local authorities, the perception of corruption, political apathy and the absence of adequate spaces for citizen participation, these conditions not only weaken the social fabric, but also hinder the development of sustainable projects that improve the quality of life of the residents of the Casacay parish. The general objective of the study is to determine how citizen involvement can have an impact on the strengthening of social management in Casacay. Specific goals include the identification of the main difficulties faced by the community in actively participating, the determination of effective ways for citizens to contribute to the development of community programmes and projects, and the formulation of strategies to encourage greater participation in social management processes. The methodology used in the titling work was based on a mixed approach, combining quantitative and qualitative methods. Surveys were carried out with the inhabitants of Casacay to collect data on their perceptions, experiences and levels of participation in community affairs, and interviews were conducted with the head of citizen participation of the GAD Pasaje, the president of CONAGOPARE EL ORO and the representative of the parish GAD, to understand the dynamics of social management and the specific challenges of the territory. The data obtained were analysed using statistical techniques and qualitative interpretation, which allowed for the identification of key patterns and relationships in the local context. The results of the research showed limited citizen participation in Casacay, mainly attributed to distrust in institutions, lack of transparency in the management of resources and the scarce promotion of spaces for dialogue and consultation. However, positive factors were also identified, such as the interest of a certain level of the population in becoming more actively involved if they are given the appropriate tools and opportunities, among the priority needs were the improvement of basic infrastructure, the implementation of educational programmes and the promotion of cultural and recreational activities. The proposal presented seeks to implement a community management plan with local governments such as the municipal and parish governments in order to improve the management of resources for projects in the parish of Casacay, transforming the current dynamics through the construction of a participatory model that promotes social cohesion, transparency and active collaboration between all the actors involved. In this way, it is expected to contribute significantly to the well-being of the community together with the parish government.
El presente trabajo de titulación aborda la incidencia del involucramiento ciudadano en el fortalecimiento de la gestión social de la parroquia Casacay, perteneciente al cantón Pasaje. El trabajo se enfoca en identificar las barreras y desafíos que limitan la participación activa de los habitantes en la toma de decisiones comunitarias, así como en proponer estrategias que promuevan un mayor compromiso y cohesión social en la región. El problema central identificado radica en el limitado involucramiento ciudadano, situación que afecta negativamente la capacidad de la comunidad para organizarse y enfrentar problemas comunes de manera efectiva. entre los factores principales que contribuyen a esta problemática se encuentran la falta de confianza en las autoridades locales, la percepción de corrupción, la apatía política y la ausencia de espacios adecuados para la participación ciudadana, estas condiciones no solo debilitan el tejido social, sino que también dificultan el desarrollo de proyectos sostenibles que mejoren la calidad de vida de los residentes de la parroquia Casacay. El objetivo general del estudio es determinar cómo el involucramiento ciudadano puede incidir en el fortalecimiento de la gestión social en Casacay. Para ello, se plantearon metas específicas que incluyen la identificación de las principales dificultades que enfrenta la comunidad para participar activamente, la determinación de formas efectivas de contribución ciudadana al desarrollo de programas y proyectos comunitarios y la formulación de estrategias para fomentar una mayor participación en los procesos de gestión social. La metodología utilizada en el trabajo de titulación se basó en un enfoque mixto, combinando métodos cuantitativos y cualitativos, se llevaron a cabo encuestas a los habitantes de Casacay para recopilar datos sobre sus percepciones, experiencias y niveles de participación en asuntos comunitarios, asimismo, se realizaron entrevistas como al jefe de participación ciudadana GAD Pasaje, al presidente del CONAGOPARE EL ORO y representante del GAD parroquial, para comprender las dinámicas de gestión social y los desafíos específicos del territorio. Los datos obtenidos se analizaron mediante técnicas estadísticas y de interpretación cualitativa, lo que permitió identificar patrones y relaciones clave en el contexto local. Los resultados de la investigación evidenciaron una participación ciudadana limitada en Casacay, atribuida principalmente a la desconfianza en las instituciones, la falta de transparencia en la gestión de recursos y la escasa promoción de espacios de diálogo y consulta, sin embargo, también se identificaron factores positivos, como el interés de cierto nivel de la población en involucrarse más activamente si se les brindan las herramientas y oportunidades adecuadas, entre las necesidades prioritarias destacaron la mejora de la infraestructura básica, la implementación de programas educativos y la promoción de actividades culturales y recreativas. La propuesta presentada busca realizar un plan de gestión comunitaria con gobiernos locales como el GAD municipal y parroquial con la finalidad de mejorar la gestión de recursos para proyectos en la parroquia Casacay, transformando las dinámicas actuales mediante la construcción de un modelo participativo que fomente la cohesión social, la transparencia y la colaboración activa entre todos los actores involucrados. De esta manera, se espera contribuir significativamente al bienestar de la comunidad conjunto con el GAD parroquial.
Keywords: INVOLUCRAMIENTO CIUDADANO; FORTALECIMIENTO; GESTION SOCIAL; PARROQUIA CASACAY